Manual development: A strategy for identifying core components of integrated health programs. (December 2015) - Mooss, Angela; Hartman, Megan; Ibañez, Gladys
Highlights: The current study used small group meetings to define and describe core components of a complex program as a means of collecting valuable process data and creating a program model manual. Results indicated that programmatic components were often implemented differently across sites and some components needed to be adapted base don stakeholder input and clinic fit/capacity. The core component descriptions and feedback were finalized into a manual which served as a tool for clinics to better understand the complex program and its parts, and as a resource for other clinics looking to adopt similar programs. Abstract: Integrated care models are gaining popularity as a clinical strategy to reduce costs and improve client outcomes; however, implementation of such complex models requires an understanding of programmatic core components essential to producing positive outcomes. To promote this understanding, evaluators can work collaboratively with organization staff and leaderships to gather information on program implementation, adaptations, organizational buy-in, and project outcomes. In 2011, SAMHSA funded two Miami health clinics to implement integrated care models in co-located settings. Changes in the federal healthcare landscape, non-Medicaid expansion for Florida, and the complexity of projects goals led evaluators to facilitate a core component review as part of evaluation. A manual was developed throughout the project and captured a description, adaptations, inputs needed, lessons learned, and sustainability for each integrated care component. To increase chances for program success, evaluators should institute a method to better define core components of new programs and implementation adaptations, while keeping program replication in mind. Breaking down the program structurally gave the evaluation utility for stakeholders, and ultimately served as a resource for organizations to better understand their program model. The manual also continues to serve as a dissemination and replication source for other providers looking to implement integrated care.